Genes and proteins of Escherichia coli K-12. - Riley, M (1998)
GenProtEC is a database of Escherichia coli genes and their gene products, classified by type of function and physiological role and with citations to the literature for each. Also present are data on sequence similarities among E.coli proteins, representing groups of paralogous genes, with PAM values, percent identity of amino acids, length of alignment and percent aligned. GenProtEC can be accessed at the URL http://www.mbl.edu/html/ecoli.html